Design and fabrication of an electrical glider to compare theoretical and experimental parameter - Hari Sharan Dangi; Prabij Joshi; Dinesh Tamang; Munna Chauhan Mahato; Nabin Bhattarai; Ram Tripathi; Bishal Poudel (Journal of Innovations in Engineering Education, 2024)
The use of Unmanned Aerial Vehicles (UAVs) is growing rapidly across many civil application domains, including real-time monitoring, wireless coverage, remote sensing, search and rescue, delivery of goods, security and surveillance, precision agriculture, and civil infrastructure inspection. Nepal, being one of the richest countries in natural resources, faces challenges daily to conserve them. With the vision of conservation and surveillance, there is a need for efficient UAVs that can replace ordinary multi-propeller drones. This project has been designed to serve the similar purpose of surveillance and agricultural growth that contribute to the technical field of the nation and promote the development of UAVs within the country. The project focuses on the design, fabrication, and testing of an efficient glider with the use of a lightweight polystyrene foam fuselage, brushless motor, propeller, servo motor, and Lithium-ion Polymer (LiPo) battery for high endurance limit. XFLR software will be used for the wing profile selection and calculation of the drag and lift coefficient, while SOLIDWORKS and ANSYS will be used for the design, simulation, and analysis of the proposed glider. The stall point for the proposed glider was found to be at a 14-degree angle of attack. The total weight of the UAV was about 800 grams with a payload of about 200 grams with a factor of safety 1.8. The glide ratio of the UAV was also compared with the theoretical glide ratio, which was found close to 3.5:1. The endurance limit of the battery was found to be about 9 minutes under loading.